Phenolic composition, antioxidant and anti-proliferative activities of edible and medicinal plants from the Peruvian Amazon - Tauchen, Jan (2016)
Among 23 extracts of medicinal and edible plants tested, Mauritia flexuosa L.f., Arecaceae, showed significant antioxidant ability (DPPH and ORAC = 1062.9 and 645.9 ± 51.4 μg TE/mg extract, respectively), while Annona montana Macfad., Annonaceae, demonstrated the most promising anti-proliferative effect (IC50 for Hep-G2 and HT-29 = 2.7 and 9.0 μg/ml, respectively). However, combinatory antioxidant/anti-proliferative effect was only detected in Oenocarpus bataua Mart., Arecaceae (DPPH = 903.8 and ORAC = 1024 μg TE/mg extract; IC50 for Hep-G2 and HT-29 at 102.6 and 38.8 μg/ml, respectively) and Inga edulis Mart., Fabaceae (DPPH = 337.0 and ORAC = 795.7 μg TE/mg extract; IC50 for Hep-G2 and HT-29 at 36.3 and 57.9 μg/ml, respectively). Phenolic content was positively correlated with antioxidant potential, however not with anti-proliferative effect. None of these extracts possessed toxicity towards normal foetal lung cells, suggesting their possible use in development of novel plant-based agents with preventive and/or therapeutic action against oxidative stress-related diseases.